2017
DOI: 10.1111/bpa.12566
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid glioblastomas stratify into established diagnostic subsets upon integrated molecular analysis

Abstract: Epithelioid glioblastoma (eGBM) is a newly defined and rare GBM variant in the current WHO 2016 classification. BRAF V600E mutation is overrepresented in these tumors and there is known some morphological overlap with anaplastic epithelioid PXA (ePXA). In order to further elucidate this diagnostic category, we molecularly characterized 64 pediatric and adult examples initially diagnosed as "eGBM." Tumors were analyzed using array based methylation and direct sequencing of the BRAF and TERT genes. Our results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 28 publications
7
88
0
1
Order By: Relevance
“…It has been suggested that a subset of anaplastic PXA and epithelioid GBM share several genetic features including BRAF V600E mutations and may be closely related to each other, if not classified in the same entity . In contrast, methylation profiling showed that epithelioid GBM may be divided into PXA and GBM, suggesting that there may be distinct subgroups . Our case strongly suggests that DNA methylation‐based diagnosis can more precisely classify anaplastic PXA, as has recently been proposed .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been suggested that a subset of anaplastic PXA and epithelioid GBM share several genetic features including BRAF V600E mutations and may be closely related to each other, if not classified in the same entity . In contrast, methylation profiling showed that epithelioid GBM may be divided into PXA and GBM, suggesting that there may be distinct subgroups . Our case strongly suggests that DNA methylation‐based diagnosis can more precisely classify anaplastic PXA, as has recently been proposed .…”
Section: Discussionsupporting
confidence: 70%
“…profiling showed that epithelioid GBM may be divided into PXA and GBM, suggesting that there may be distinct subgroups. 9 Our case strongly suggests that DNA methylation-based diagnosis can more precisely classify anaplastic PXA, as has recently been proposed. 5 It is unlikely that histology alone is sufficient to diagnose anaplastic PXA, as pleomorphic gliomas with anaplastic features include both anaplastic PXA and epithelioid GBM.…”
Section: A S E Rep Ortsupporting
confidence: 72%
“…To date, a single DNA methylation pattern sufficiently distinct for robust tumour classification has been identified for pleomorphic xanthoastrocytoma (PXA) . Currently, WHO grade II and III PXA share this DNA methylation class that was therefore named (anaplastic) pleomorphic xanthoastrocytoma .…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 99%
“…Currently, WHO grade II and III PXA share this DNA methylation class that was therefore named (anaplastic) pleomorphic xanthoastrocytoma . DNA methylation indicates that PXA may be considered as something like the chameleon of brain tumours, as tumours with this distinct molecular profile have been identified in substantial numbers among histological series of paediatric glioblastomas epithelioid glioblastomas and astroblastomas , and at lower frequency among embryonal tumours , gangliogliomas and AT/RTs . Thus, in contrast to several other discussed tumours (e.g.…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 99%
“…DNA methylation profiling of 64 histologically diagnosed eGBMs revealed a subset with a similar expression pattern to PXA that was enriched for BRAF V600E (positive in 80%). 17 Therefore, although the histologic distinction between eGBM and aPXA remains debatable based on morphology alone, the presence of either of these features in HGG (ie, epithelioid or PXA-like characteristics), as well as any IDH wild-type GBM, particularly in a patient aged <35 years, should trigger routine screening for the presence of a BRAF V600E mutation. …”
Section: Incidencementioning
confidence: 99%